Planning sentence production in aphasia: evidence from structural priming and eye-tracking - van Boxtel, Willem S.; Cox, Briana N.; Keen, Austin; Lee, Jiyeon (Frontiers in Language Sciences, 2023)
Background: Grammatical encoding is impaired in many persons with aphasia (PWA), resulting in deficits in sentence production accuracies and underlying planning processes. However, relatively little is known on how these grammatical encoding deficits can be mediated in PWA. This study aimed to facilitate off-line (accuracy) and real-time (eye fixations) encoding of passive sentences through implicit structural priming, a tendency to better process a current sentence because of its grammatical similarity to a previously experienced (prime) sentence. Method: 16 PWA and 16 age-matched controls completed an eyetracking-while-speaking task, where they described a target transitive picture preceded by a comprehension prime involving either an active or passive form. We measured immediate and cumulative priming effects on proportions of passives produced for the target pictures and proportions of eye fixations made to the theme actor in the target scene before speech onset of the sentence production. Results & Conclusion: Both PWA and controls produced cumulatively more passives as the experiment progressed despite an absence of immediate priming effects in PWA. Both groups also showed cumulative changes in the pre-speech eye fixations associated with passive productions, with this cumulative priming effect greater for the PWA group. These findings suggest that structural priming results in gradual adaptation of the grammatical encoding processes of PWA and that structural priming may be used as a treatment component for improving grammatical deficits in aphasia.